A comprehensive characterisation of the metabolic profile of varicose veins; implications in elaborating plausible cellular pathways for disease pathogenesis - Anwar, Muzaffar A.; Adesina-Georgiadis, Kyrillos N.; Spagou, K.; Vorkas, P. A.; Li, J. V.; Shalhoub, Joseph; Holmes, Elaine; Davies, Alun H. (Scientific reports, 2017)
Metabolic phenotypes reflect both the genetic and environmental factors which contribute to the development of varicose veins (VV). This study utilises analytical techniques to provide a comprehensive metabolic picture of VV disease, with the aim of identifying putative cellular pathways of disease pathogenesis. VV (n = 80) and non-VV (n = 35) aqueous and lipid metabolite extracts were analysed using 600 MHz 1 H Nuclear Magnetic Resonance spectroscopy and Ultra-Performance Liquid Chromatography Mass Spectrometry. A subset of tissue samples (8 subjects and 8 controls) were analysed for microRNA expression and the data analysed with mirBase (www.mirbase.org). Using Multivariate statistical analysis, Ingenuity pathway analysis software, DIANALAB database and published literature, the association of significant metabolites with relevant cellular pathways were understood. Higher concentrations of glutamate, taurine, myo-inositol, creatine and inosine were present in aqueous extracts and phosphatidylcholine, phosphatidylethanolamine and sphingomyelin in lipid extracts in the VV group compared with non-VV group. Out of 7 differentially expressed miRNAs, spearman correlation testing highlighted correlation of hsa-miR-642a-3p, hsa-miR-4459 and hsa-miR-135a-3p expression with inosine in the vein tissue, while miR-216a-5p, conversely, was correlated with phosphatidylcholine and phosphatidylethanolamine. Pathway analysis revealed an association of phosphatidylcholine and sphingomyelin with inflammation and myo-inositol with cellular proliferation.